(untitled) (Journal of Hama University, 2022)
Introduction: studying the relationship between body image and self-concept provides an important basis in applied fields of mental health, to undertake preventive efforts in this field and prevent the increased risk of mental disorders among soldiers who have been subjected to physical distortions caused by wars. Purpose: assess the body image, self-concept and relationship between them among military personnel who suffered physical injuries. Methods: A correlational descriptive study was conducted on a convenient and available sample of 100 injured Syrian Arab Army soldiers, in the plastic and reconstructive surgery department at Tishreen University Hospital in Lattakia of the Ministry of Higher Education, Al-Assad Military Hospital, Zahi Azraq Hospital and in the rehabilitation centers in Lattakia. And places of residence of war casualties. Data were collected using two pre-prepared body image and self-concept scales. Results he results showed a statistically significant inverse relationship between dissatisfaction with body image and self-concept among the army’s victims with physical deformities resulting from the war, and that nearly half of the study participants, 48%, have an average level of satisfaction with body image, while about a quarter of them 26% have a good level of satisfaction. Less than two-thirds of them, 62%, have an intermediate level of self-concept, while about a quarter of them, 27%, have a high level of self-concept. Recommends: The study recommended designing counseling nursing programs to improve the level of body image and self-concept of people with deformities caused by war, increase the social and psychological support provided, and conduct more in-depth research and studies to find out the reasons and motives behind the low level of satisfaction with body images and self-concept.